Antimicrobial Resistance – A Silent Pandemic - Sneka P; Sangamithrav; Mahalakshmi K (National Journal of Community Medicine, 2023)
Antimicrobial resistance is posing a great threat in many low and middle income countries as a result of groundless and unseemly use of antimicrobial agents in the community. Research related to antimicrobial use, determinants and development of antimicrobial resistance, regional variation and interventional strategies according to the existing health care situation in each country is a big challenge.